The Name Is the Game: Nicknames as Predictors of Personality and Mating Strategy in Online Dating - Lange, Benjamin P.; von Andrian-Werburg, Maximilian T. P.; Adler, Dorothea C.; Zaretsky, Eugen (Frontiers in Communication, 2019)
Objective: We investigated the communicative function of online dating nicknames. Our aim was to assess if it is possible to correctly guess personality traits of a user simply by reading his/her nickname. Method: We had 69 nickname users (average age: 33.59 years, 36 female) complete questionnaires assessing their personality (Big 5 + narcissism) and mating strategy (short- vs. long-term). We then checked (using a total of 638 participants, average age: 26.83 years, 355 female), whether personality and mating strategy of the nickname users could be assessed correctly based only on the nickname. We also captured the motivation to contact the user behind a nickname and looked at linguistic features of the nicknames. Results: We found that personality and mating strategy could be inferred from a nickname. Furthermore, going by trends, women were better at intersexual personality judgments, whereas men were better in intrasexual judgements. We also found several correlates of the motivation to contact the person behind the nickname. Among other factors, long nicknames seemed to deter people from contacting the nickname user. Conclusions: Findings display that humans are capable of making accurate personality judgements in computer-mediated communication by means of even small cues like nicknames.